The role of microbiota in the pathophysiology of uterine fibroids – a systematic review - Korczynska, Lidia; Zeber-Lubecka, Natalia; Zgliczynska, Magdalena; Zarychta, Elzbieta; Zareba, Kornelia; Wojtyla, Cezary; Dabrowska, Michalina; Ciebiera, Michal (Frontiers in Cellular and Infection Microbiology, 2023)
For a long time, the uterus had been considered a sterile organ, meaning that under physiological conditions the uterus would not be colonized by bacteria. Based on available data, it may be concluded that the gut and uterine microbiome are related and that the role of this microbiome is greater than expected. Despite being the most common pelvic neoplasms in women of reproductive age, uterine fibroids (UFs) are still mysterious tumors whose etiology has not been fully determined. This systematic review presents the relationship between intestinal and uterine dysbiosis and uterine fibroids. A systematic review of three medical databases was carried out: the MEDLINE/PubMed, Scopus and Cochrane. In this study, 195 titles and abstracts were reviewed, including only original articles and clinical trials of uterine microbiome criteria. Finally, 16 studies were included to the analysis. In recent years, researchers dealing with reproduction in a broad sense have focused on the microbiome in various locations to study its role in the pathogenesis and, consequently, the prevention and treatment of diseases of the genital organ. Conventional microbial detection methods are not suitable for identifying bacteria, which are difficult to culture. Next-generation sequencing (NGS) provides an easier and faster analysis of bacterial populations. It seems that gut microbiota dysbiosis has the potential as a risk factor for uterine fibroids. Some changes were shown in many types of bacteria, such as Firmicutes, Proteobacteria, Actinobacteria and Verrucomicrobia detected in fecal samples in patients with uterine fibroids. In view of the few results on the link between the microbiome and uterine fibroids, further intensive studies in humans and animal models are necessary, including the possible use of different microbiome modulations in the prevention or treatment of uterine fibroids.